Structural Competency: A Faculty Development Workshop Series for Anti-racism in Medical Education - Shani R. Scott; Cristina M. Gonzalez; Chenshu Zhang; Iman Hassan (MedEdPORTAL)
Introduction In response to accreditation bodies requiring health disparities curricula, medical educators are tasked with incorporating structural competency, the understanding of how social and structural barriers like structural racism impact health, into their teaching. Most have not received training in this area, yet there remains a scarcity of faculty development curricula to address this gap. We describe the creation, implementation, and evaluation of a faculty development workshop series rooted in the framework of structural competency. Methods We delivered four 90-minute workshops at an urban academic medical center from March through April of 2021. Workshops were offered to interdisciplinary faculty. We evaluated this workshop series with a pre- and postintervention survey assessing attitudes and confidence, and a postintervention satisfaction survey. Data analysis was conducted using a paired t test. Results A total of 206 participants attended at least one workshop within the series, and 20 participants completed both pre- and postintervention surveys. Participants overwhelmingly recommended these workshops to their colleagues and had significant increases in overall attitudes (3.3 vs. 3.6, p = .001) and level of confidence (3.2 vs. 3.9, p < .001) incorporating structural competency. Discussion Our application of structural competency to faculty workshops and teaching tools feasibly engages faculty in instruction to incorporate concepts of structural racism and the downstream effects of social determinants of health into clinical teaching. It represents an innovative tool as we seek to enhance clinical teaching to improve care for racially and ethnically minoritized communities.